In-vitro micrografting technique in sweet orange (Citrus sinensis) cv. Blood Red to produce virus free plants - KANWAR, JYOTI; KAUL, M K; NARUKA, I S; SINGH, P P (The Indian Journal of Agricultural Sciences, 2019)
This study was carried out to assess the potential use and applicability of micrografting technique for the development of virus free nursery in sweet orange (Citrus sinensis Osbeck) cv. Blood Red Malta. The micro grafting was carried out using 11-20 days old etiolated seedlings of Rough Lemon, Sour orange, Carrizo and Karna Khatta rootstocks. An apical meristem (1-2 mm) having 3-leaf primordial (0.3-0.5 mm) were taken from the axillary proliferated nodal segments. Finely excised meristems were placed on aseptically grown rootstocks making an inverted ’T’ incision in vitro. Micro grafts were inoculated on MS media added with different Plant Growth Regulators, i.e. IAA, NAA and 2,4-D each under varied concentrations (control, 0.1 ppm, 0.5 ppm, 1.0 ppm , 1.5 ppm, 2.0 and 3.0 ppm). Highest grafts success (60%) was recorded when 13 days old Carrizo seedlings were used as rootstock. Among all the treatments, scion treated with 2,4-D at 3.0 mg/l exerted maximum positive effect on the success of STG (70.00%). Overall, Sweet orange cv. Blood Red, micro grafted on Carrizo rootstock culturing on liquid MS media containing 2, 4-D at 3.0 mg/L resulted maximum success and growth of grafts. Successful micrografts were hardened under controlled conditions and further shifted in insect proof net house to develop disease free mother progeny.